THE INFLUENCE OF AUDIT DELAY, SIZE OF PUBLIC ACCOUNTING FIRM, AUDIT OPINION, AND MANAGEMENT CHANGE ON AUDITOR SWITCHING - Wahyuni, Lidia; Salim, Agus; Murtanto; Pertiwi, Arinda Deswanti; Rahmandika Adipradana (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2024)
This study explores the impact of audit delay, the size of public accounting firms, audit opinions, and management changes on auditor switching among companies listed on the Indonesia Stock Exchange. The research aims to identify the key factors that influence a company's decision to switch auditors. Using logistic regression analysis and secondary data from financial reports, the study introduces a unique approach by simultaneously analyzing four independent variables, which is rarely done in prior studies. The results reveal that audit delay and management changes significantly affect auditor switching, while the size of public accounting firms and audit opinions do not have a significant impact. The findings suggest that operational and managerial factors play a more critical role in auditor switching decisions compared to financial factors. Theoretically, the study supports the relevance of agency theory in explaining auditor switching, particularly in addressing conflicts of interest between management and shareholders. Practically, these results provide valuable insights for company management when deciding to switch auditors and highlight the importance for regulators to implement policies that enhance transparency and audit quality, strengthening corporate governance practices in Indonesia.